Exploring the hydrophobic effects of quaternary ammonium copolymers on corrosion of casing and tubing steel in acidic solution - Ghadeer Mubarak; Chandrabhan Verma; Mohammad A. Jafar Mazumder; Imad Barsoum; Akram Alfantazi (PLoS ONE, 2025)
By encouraging improved adsorption onto metal surfaces and creating a more powerful barrier against corrosive chemicals, the hydrophobic property of corrosion inhibitors raises inhibition efficiency and decreases corrosion rates. This work aims to synthesize and describe three quaternary ammonium-based copolymers (AMCs) with different hydrophobic qualities and investigate their ability to inhibit P110 CS corrosion in 15% HCl, which is helpful for casing and tubing. The results showed that AMCs act as efficient corrosion inhibitors, with over 90% inhibition efficiency (%IE ) at 20 ppm concentration. The electrochemical investigation results indicated that the AMCs with hydrophilic and hydrophobic ratios of 100 (5), 90:10 (6a), and 80:20 (6b) manifest %IE of 87.74%, 92.12%, and 93.53%, respectively. The electrochemical investigations show that at the metallic surface’s active areas, AMCs successfully replace the pre-adsorbed water molecules. They are categorized as mixed-type corrosion inhibitors because they prevent both anodic and cathodic reactions without appreciably changing the corrosion potential (Ecorr). Their adsorption on the metallic surface follows the Langmuir adsorption isotherm. Surface analysis tools like SEM and EDX are utilized to investigate the corrosion prevention mechanism of adsorption. The DFT analysis results show that quaternary nitrogen atoms of hydrophilic and hydrophobic moieties play a key role in the adsorption and charge-sharing processes. Finally, the corrosion prevention mechanism of AMCs is explained using a graphic depiction based on the ideas of electrochemical, surface, and computational studies.